Effects of zinc supplement on tumorigenic (MCF-7) and non-tumorigenic (MCF-10A) mammary epithelial cells under different oxygen conditions - Lee, Sze Yen (2013)
Zinc is an important trace element which is obtained through our daily food intake. Its imbalance causes a range of human diseases from simple headaches to cancer. Insufficient zinc is addressed with the use of zinc supplements mostly in the form of tablets. The importance of zinc level in the normal homeostasis of the human body highlights the need for further understanding of zinc involvement in cellular regulation. Changes in human physiology also affect the outcome of zinc functions. These changes in women are more common due to conditions such as pregnancy, lactation and menopausal changes. Earlier studies reported that malignant breast tissues were commonly found to correlate with high cellular zinc concentration. Further studies on the outcome of high cellular zinc concentration on the cellular functionhowever were never reported until now. To address this issue, this study was conducted to investigate the effects of zinc supplement on tumorigenic MCF-7 and non-tumorigenic MCF-10A mammary epithelial cells. It was hypothesized that zinc supplement will cause the cell cycle control mechanisms of breast epithelia to be deregulated. Results obtained showed that the cells responded differently to zinc treatment beginning at 100 μM zinc, but not at lower concentrations. MCF10-A was found to be arrested at the G2/M cell phase at higher level compared to the MCF-7 cells. Conditions of normoxia and hypoxia did not drastically affect the way that the MCF-7 and MCF-10A responded to zinc treatment. The G2/M arrest was found to be associated with the increase in Cyclin A in both cell lines. In MCF-10A, p21CIP1/WAF1 protein was increased but not in MCF-7. This perhaps contributed to the higher G2/M population in zinc-treated MCF-10A. Interestingly, a hypoxia-inducible factor alpha (HIF-1a), a monomer of the HIF-1 transcription factor also became accumulated in the presence of zinc, in both MCF-7 and MCF-10A cells. The HIF-1 complex was found to be active via detection of the CAIX expression, its specific transcriptional target. Overall, data obtained from this study contribute to further understanding of zinc in the regulation of breast epithelial cells. The information can be used to assist future research in the correlation of zinc and the development of breast cancer as well as other types of cancers in human.